The effect of exercises accompanying biomechanical feedback on some kinematic variables and the performance of the forehand smash skill of badminton (Journal of the College of Basic Education, 2024)
Feedback is considered one of the most important methods that contribute effectively to correcting errors and developing levels for players because it contains additional corrective information that serves skill work. Here in this research, the effect of biomechanical feedback is studied with the learner’s participation to analyze his motor performance and compare with a model to modify his performance after discovering errors. Which is diagnosed when performing the skill of the front smash of badminton, which is one of the basic skills on which learning of many other skills depends.This research aimed to analyze the kinetics of the performance of the front smash skill and compare it with the biomechanical variables of one of the models, identifying the effect of biomechanical feedback on the performance of the front smash skill, as the research suggests that there are statistically significant differences between the pre- and post-tests in the performance of the front smash skill. Forward overwhelming, the researcher used the experimental method With a one-group design with two pre and post tests to suit the nature of the research, where the study concluded that the biomechanical feedback contributed effectively through the educational curriculum in influencing the biomechanical variables and in improving the performance of the front crushing blow, which contributed to improving the level of the player, and the study recommended to rely on Biomechanical feedback for correction Mistakes in skill performance, especially the front smash shot, the use of biomechanical feedback during practical lessons, or at least presenting the skill performance to the learner versus a model performance for the learner to compare between them.